A simplified method and numerical simulation for wedge-shaped plunger wavemaker. (1st December 2021) - Sun, Bin; Li, Cheng; Yang, Shaolin; Zhang, Haijia
Abstract: The wave can be obtained by the horizontal movement of the piston-plate or flap-plate, and also could be obtained by the vertical movement of the wedge. In this paper, Firstly, the implicit equations of the relationship between the wedge vertical motion trajectory and the targeted wave including linear wave, stokes-fifth-order wave, solitary wave and irregular wave, are derived. Secondly, the RNG k-ε turbulence model and VOF method are combined to solve the RANS equations for wave-making of targeted wave by wedge-shaped plunger wavemaker using CFD software Fluent. Thirdly, the numerical results are compared with the analytical solutions systematically, also the characteristics of the wave surface, velocity field, water particle trajectories, as well as their evolution and propagation are elaborately explored. Meanwhile, the effect of the initial entry depth and the wedge angle on the wave-making quality was discussed, and the differences in the force and power between wedge-shaped plunger wavemaker and piston-type wavemaker are compared in detail. The velocity field and water particle trajectories present a comprehensive understanding of wave generation and propagation. The results indicate that the proposed simplified method and numerical simulation have high accuracy for linear wave, weakly-nonlinear stokes-fifth-order wave, solitary wave and irregular wave. Highlights: Equations are derived to generate linear wave, Stokes fifth-order wave, solitary wave, irregular wave by wedge-shaped plunger wavemaker. Wave surface, velocity field, pressure field for four types of waves are investigated systematically. Evolution and propagation of the water particle trajectories are elaborately explored to investigate the wave formation process. The effect of the initial entry depth and the wedge angle on wave-making quality are discussed. The differences of the force and power between wedge-shaped plunger wavemaker and piston-type wavemaker are compared.